0776 SLEEPHEALTH MOBILE APP STUDY: BRINGING THE SLEEP LAB TO YOU. (28th April 2017) - Deering, S; Amdur, A; Borelli, J; Drobnich, D; Headapohl, W; Stepnowsky, CJ
Abstract: Introduction: Conducting research using personal smartphones is a novel approach to the study of health and disease that is only beginning to be meaningfully explored. The SleepHealth Mobile App study utilized Apple's open source ResearchKit framework to deploy a smartphone app based research study directly to participants with the aim of developing a better understanding of the relationship between sleep habits and daytime functioning. Methods: SleepHealth launched March, 2016 on the Apple App Store. Users downloaded the app, learned about the study via study website and the app, and signed up using an electronic informed consent process. The study was comprised of questionnaires and activities that assessed sleep quality and daytime functioning. This included sleep habits, AM/PM check-ins, alertness and sleepiness tracking, and a nap tracker. Results: Since launch, SleepHealth was viewed 47, 847 times and downloaded 17, 699 times, resulting in 9, 499 total participants. Our sample was approximately 76% male with a mean age of 36.9 (SD=13.1). 40% believed that they had a sleep problem, and about 40% had mentioned this to a clinician. 50% reported that they did not take naps, and about 60% reported that they were very dependent on their alarm clocks, suggesting they may be sleep deprived. 55% reported having flexible work hours. Of note, 65% of our sample had never participated in a research study before. Conclusion: Our experience to date shows that use of a mobile application to conduct a study of sleep and daytime functioning is feasible and scalable. Clear advantages of using the ResearchKit platform are costs, ease of deployability, participant reach, and ability to query participants on a daily basis outside of a traditional laboratory setting. Limitations are that the research is not being carried out in a controlled environment and is currently limited to Apple users. Support (If Any): N/A.